Calculating the carbon footprint in the supply chain of a heating company - Śniegowski, Maciej (Instal, 2024)
The need to reduce greenhouse gas (GHG) emissions is driven by global efforts to mitigate the effects of climate change. This article presents the concept and legal requirements for calculating the carbon footprint of a district heating company’s supply chain. The focus is on the Corporate Sustainability Reporting Directive (CSRD), which amends the 2014 Non-Financial Reporting Directive (NFRD).
Keywords: carbon footprint; supply chain; heating; environmentally sustainable activities